Survival and prognostic factors among different types of liposarcomas based on SEER database - Jiaqi Zhao; WenLi Du; XiaoLiang Tao; AiAi Li; Yi Li; Shuai Zhang (Scientific Reports)
Abstract The aim of this study is to elucidate the disparities in survival and risk factors among different subtypes of liposarcoma, through analysis of epidemiological and prognostic data. The study cohort consisted of 12,822 patients diagnosed with liposarcoma in the United States between 2000 and 2021, whose data were retrieved from the Surveillance, Epidemiology, and End Results (SEER) program. The prognosis for different subtypes of liposarcoma and the associated factors such as age, tumor stage, intervention, gender, tumor grade, location, size, chemotherapy and radiotherapy, were retrieved from the database. Well-differentiated liposarcoma demonstrated the most favorable prognosis, with 5-year and 10-year survival rates of 82% and 68%, respectively, followed by myxoid liposarcoma, pleomorphic liposarcoma and dedifferentiated liposarcoma, which exhibited the poorest prognosis. Advanced age, higher tumor stage, and the absence of surgical intervention were associated with inferior survival outcomes across all subtypes. Male gender, higher pathological grade, and primary tumor sites outside the extremities were identified as risk factors for the prognosis of subtypes other than pleomorphic liposarcoma. Larger tumor size was an indicator of a worse prognosis in subtypes other than well-differentiated liposarcoma. Chemotherapy was a risk factor for the prognosis of well-differentiated and myxoid liposarcomas but had no significant correlation with the prognosis of pleomorphic and dedifferentiated liposarcomas. Radiotherapy served as a protective factor for the prognosis of subtypes other than well-differentiated liposarcoma. Survival and prognostic factors vary among the major subtypes of liposarcoma, necessitating individualized analysis for each subtype. Poorer outcomes can be anticipated in the dedifferentiated and pleomorphic subtypes, while well-differentiated and myxoid liposarcomas exhibit relatively favorable prognoses.